Group Work: Effect of Cooperative Learning Method on Academic Performance in English Language among Pupils in Universal Primary Education Schools in Kashari, Uganda - Namusoke, Edith; Rukundo, Aloysius (Cogent Education, 2022)
As compared to traditional modes of delivery, cooperative learning (CL), as a teaching method, is said to be effective in improving learners’ academic achievement. A plethora of studies underscore CL as a strategy of instruction that delivers improvement in learning outcomes. However, not many of the studies consider the role of CL in facilitating pupils’ learning in English language, and in universal education primary schools. This study explores the role of cooperative learning in performance of primary school learners in English language. The study employed a quasi-experimental design to investigate how CL affected performance in the experimental group. A purposive sample of 180 primary seven pupils in two Universal Primary Education (UPE) schools was considered. The schools were selected using simple random sampling (rotary method). Observation checklists and classroom tests for English language were used to collect the data. Assessment was done at the baseline and after treatment. There were no statistically significant differences in pupils’ performance in English language at the baseline assessment. After treatment, CL had a statistically significant effect (Mean difference = −5.07, Cohen’s d = −1.84, p < .001) on the performance of pupils in the experimental group. As a pupil-centred learning method, CL could be an impactful teaching-learning strategy for English language.
Keywords: Cooperative learning; Group work; Experiment; Performance; Learning methods